Sistem Pelaporan Data Capaian Standar Pelayanan Minimal Bidang Kesehatan Berbasis Website - Nugrah Satria Bagassabirin; Acihmah Sidauruk; Erni Seniwati; Wiwi Widayani; Agung Nugroho (Sekawan Institut, 2025)
Reporting the achievement of Minimum Service Standards in the health sector (SPM BK) plays a crucial role in evaluating and improving healthcare services. the reporting of Minimum Service Standards (SPM BK) achievement data at the Sumbawa District Health Office is not standardized, with inconsistent report formats and submissions via third-party messaging applications (WhatsApp). This leads to delays, data inconsistencies, and calculation errors, which affect the quality of monitoring. This study aims to design and develop a web-based information system to facilitate the reporting and monitoring of SPM BK achievements at the Sumbawa District Health Office. The web-based system enables easier reporting and monitoring, while the processing of SPM BK data can be automated to reduce the potential for human error. The system development followed the Waterfall model, starting from data collection through interview methods, system needs analysis, system design using Entity Relationship Diagram, Use Case Diagram, and Wireframe, followed by the system development process using Laravel 10 and MySQL database, and closed with the testing stages using the black box method, and User Acceptance Testing (UAT). The UAT results showed a success rate of 84.7% with a